(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Namita Gokhale is an Indian novelist who builds up her works with a different vision. She creates her own signature on the contemporary Indian women’s literature list with her frank presentation of the realities of life. Namita Gokhale’s Paro: Dreams of Passion (1984) presents a study of love and sexual liberation in women of the Indian scenario. Through her characters, she depicts women and men’s status in society and their relationships through real-time experiences. She covers urban life in her first novel, Paro: Dreams of Passion, which explores men and women’s lifestyles. She succeeds in presenting alternative realities with her new woman voice ’Paro’ who is searching for herself. Identity and self-autonomy with liberation.